Validation of health educational technology on “home enteral nutritional therapy” for elderly careers (Research, Society and Development, 2020)
Objective: To describe the content and appearance validation process of a guideline for guidance to elderly caregivers in home enteral nutrition therapy (TNED). Method: Methodological study in four stages: approval by a research ethics committee, bibliographic survey, preparation of a booklet and validation by material specialists by specialists in the subject. Ten experts from the nutrition course at higher education institutions in Teresina - PI participated in the validation. The minimum Content Validity Index (CVI) of 0.78 and the minimum agreement of 75% were considered for appearance validation. Results: The content and appearance of the booklet were validated with a CVI of 0.95 by the judges and an excellent level of agreement (80% - 100%), characterized as nutritionists, masters and / or doctors with expertise in health education and practical experience, research and publication in one of the study's areas of interest. The judges contributed with suggestions that were accepted to improve the booklet in its final version. Conclusion: The booklet was validated in content and appearance, constituting a relevant and easy to use instrument in health education actions carried out, especially by professionals from the Family Health Strategy with caregivers of elderly people in TNED.